Comparison of knowledge, attitudes and practices on prevention and control measures in dengue infection between families with or without dengue cases after “El Niño Costero” phenomenon at the District of Palpa - Ica during January's 2019 - Cruz Cutty, Lourdes Marylin (2020)
Introduction: Dengue is an endemic disease in Peru and is considered a public health problem. During and after the “El Niño Costero” phenomenon in 2017, the Department of Ica presented 4384 cases of dengue, the highest number of cases in this region. Methods: A cross-sectional analytical study was conducted and included all the families in the district of Palpa, Ica. The main exposure was the report of a previous dengue infection of any family member and we want to find an association with the level of knowledge, attitudes and practices about dengue. Results: We found that the participants who had been exposed to dengue had a 63% higher probability (PR: 1.63; 95% CI: 1.02 - 2.58) of having a high level of knowledge about dengue in comparison with the participants of families who did not have a history of dengue. For the levels of attitudes (PR: 0.90; IC 95%: 0.60 – 1.35) and practices (PR: 0.88; IC 95%: 0.51 – 1.51) no statistically significant differences were found. Conclusions: Our study found that previous exposure to dengue is associated with a high level of knowledge but, it is not associated with a high level of attitude or practices in families in the district of Palpa-Ica.